Congenital Facial Paralysis Revealing an Aplasic Facial Nerve: A Report of Two Cases. (21st May 2022) - Tomé, Sónia; Matos, Joana; Barreto, José; Carvalho, João; Leal, Joana; Aguiar Branco, Catarina
Abstract: Congenital facial palsy is a rare condition, usually related to a traumatic event during birth or as a feature of a syndrome. In this report, two cases of infants with peripheral facial palsy since birth are described, in which magnetic resonance imaging demonstrated unilateral aplasia of the facial nerve. There are only a few cases with similar findings described in the literature. A multidisciplinary approach is recommended to provide the best care. Although no reinnervation of the facial muscles is likely to occur, rehabilitative therapies may be valuable as complementary treatments.